2019
DOI: 10.1590/0074-02760190004
|View full text |Cite
|
Sign up to set email alerts
|

Association between MBL2 haplotypes and dengue severity in children from Rio de Janeiro, Brazil

Abstract: BACKGROUND Dengue is an arthropod-borne viral disease with a majority of asymptomatic individuals and clinical manifestations varying from mild fever to severe and potentially lethal forms. An increasing number of genetic studies have outlined the association between host genetic variations and dengue severity. Genes associated to viral recognition and entry, as well as those encoding mediators of the immune response against infection are strong candidates for association studies. OBJECTIVES The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…However, Xavier-Carvalho et al (2013) found no statistical difference in the frequency of CCR5Δ32 polymorphism between Brazilian children with severe DENV infection and healthy controls. In the same direction, no effect of CCR5Δ32 on susceptibility to DENV infection was found in a small sample-size study performed with individuals from Western Australia (Brestovac et al, 2014) and recent data suggested no important involvement of CCR5 gene or CCR5 polymorphisms in DENV infection (Cahill et al, 2018;Ornelas et al, 2019). Finally, the CCR5Δ32 allele was not identified in a small group of Indian DENV-infected individuals (Islam et al, 2019).…”
Section: Dengue Virusmentioning
confidence: 85%
“…However, Xavier-Carvalho et al (2013) found no statistical difference in the frequency of CCR5Δ32 polymorphism between Brazilian children with severe DENV infection and healthy controls. In the same direction, no effect of CCR5Δ32 on susceptibility to DENV infection was found in a small sample-size study performed with individuals from Western Australia (Brestovac et al, 2014) and recent data suggested no important involvement of CCR5 gene or CCR5 polymorphisms in DENV infection (Cahill et al, 2018;Ornelas et al, 2019). Finally, the CCR5Δ32 allele was not identified in a small group of Indian DENV-infected individuals (Islam et al, 2019).…”
Section: Dengue Virusmentioning
confidence: 85%
“…2), the rs7916582 polymorphism was not found to be significantly associated with TB susceptibility. However, when the rs10824793 and rs7916582 SNPs were combined in haplotypes, the rs10824793*G/ rs7916582*T and rs10824793*G/rs7916582*C alleles were found to be significantly associated with TB risk, which is similar to the haplotype block rs7095891*G/ rs1800450*C/rs1800451*C/rs4935047*A/rs930509*G/ rs2120131*G/rs2099902*C yielded by LD analysis in a previous study [31]. LD is the non-random combination of alleles at different loci and is influenced by several factors, such as selection, genetic drift, recombination rate, mutation rate, and population structure as well as genetic linkage.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, it was also shown to be associated with sodium-lithium countertransport (SLC) and systolic blood pressure [29]. Previous studies have found no association between rs2099902 and recurrent vulvovaginal infections risk [30] or severe dengue [31]; however, another study performed by Zanetti et al suggested that rs2099902 was associated with increased risk of colon cancer in African Americans [32]. These data indicate that the susceptibility and pathogenicity of the same SNP were different in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the MBL2*OO genotype, the MBL2*O allele and MBL2 haplotypes, which correlate with low MBL levels have been shown to be associated with DHF in a Brazilian study group 18 . A recent study has also shown an www.nature.com/scientificreports/ association of MBL2 haplotypes with an increased risk of dengue severity in Brazilians 19 . However, no association between MBL2 polymorphisms and DENV infection was observed in a Thai study group 24 .…”
Section: Discussionmentioning
confidence: 90%
“…A previous study has indicated direct complement restriction of DENV infection via MBL recognition of the high-mannose glycans of DENV envelope proteins 16 . In addition, MBL2 polymorphisms have been shown to be associated with dengue severity in Brazilian and Thai populations 17 19 . The above studies have investigated only the contribution of MBL2 polymorphisms and MBL serum levels.…”
Section: Introductionmentioning
confidence: 99%